Smoking Behavior Among Students at SMPN 22 in Cemorokandang Village, Kedungkandang District, Malang City - Awani, Septiara Balqisya; Lala, Handy (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Smoking behavior is a habit that is still commonly found among adolescents, including students at SMPN 22 Malang City. Adolescents are in a phase of psychosocial development that is highly susceptible to environmental influences, such as peers, family, and social communities. Objectives: This study aims to investigate students' smoking behavior and the factors contributing to it, including perceptions, motivations, and school policies in addressing it.Methods: The study employs a qualitative method with a phenomenological approach, involving 30 informants comprising students, homeroom teachers, guidance counselors, student affairs teachers, and the school principal. Data were collected through in-depth interviews and observations.Results: The results of the study indicate that smoking behavior among students is influenced by three main factors: predisposing factors (students' good knowledge is not aligned with their attitudes toward smoking), enabling factors (easy access to cigarettes, lack of supervision, and limited health information about smoking), and reinforcing factors (social support from peers, smoking family members, and teenage lifestyle). Additionally, students' motivation to smoke is related to curiosity, emotional release, stress, and identity formation.Conclusion: The conclusion of this study indicates that smoking behavior is the result of a complex interaction between individual and social environmental factors. Therefore, a collaborative approach between schools, parents, and external agencies is needed through more stringent and targeted policies and education to reduce smoking rates among adolescents in schools.